A comprehensive review of ethnobotanical plants used by the people of Pir Panjal Range in (Jammu Division) Union Territory Himalaya of Jammu and Kashmir- India - Mahmood, Tahir (International Multidisciplinary Research Journal, 2020)
The current paper provides a taxonomic inventory of the medicinal plant species collected by the author during the last one decade from Pir Panjal range in (Jammu Division) Himalaya of Union territory Jammu & Kashmir- India. The inventory records a total no of 76 medicinal species belonging to 45 families of the total taxa were recorded for the medicinal Purposes. The inventory is expected to provide baseline scientific data for further studies on plant diversity in Jammu division and can be used to facilitate the long-term conservation and sustainable use of medicinal plant resources in the Himalaya region, and among all the families Cucurbitaceae and Euphorbiaceae were found to be most dominant families in term of the species in the areas with 06 species, followed by Polygonaceae and Rosaceae.